The Development of Facial Lipofilling from a Historical Point of View - van Dongen, Joris A.; van Boxtel, Joeri; Harmsen, Martin C.; Stevens, Hieronymus P. (Facial Plastic Surgery, 2019)
Lipofilling, the transplantation of adipose tissue, has already been used since the end of the 19th century. For decades, lipofilling was used to restore loss of volume due to aging, trauma, or congenital defects. Later on, the indications for the use of lipofilling expanded by treating aged skin, scars, and improving wound healing. The expansion was caused by the discovery of adipose derived stromal cells (ASCs) in adipose tissue and the development of very fine harvesting and injection cannulas which made it possible to inject small adipose tissue particles in small volume areas, such as the face. ASCs are multipotent stromal cells which reside in the stromal vascular fraction (SVF) of adipose tissue and are able to differentiate in multiple cell lineages and secrete a plurality of growth factors with regenerative potentials. The discovery of ASCs led toward more experimental cell-based therapies, that is, ASCs or SVF isolated by means of enzymatic isolation procedures. Later on, enzymatic isolation procedures were forbidden in many countries by legislation and were replaced by mechanical isolation procedures, such as the Nanofat and Fractionation of Adipose Tissue (FAT) procedures. The Nanofat procedure has been extensively investigated, especially as treatment for skin rejuvenation in the face. Though, substantial evidence is lacking for using facial lipofilling or any therapeutic component, that is, ASCs or SVF for skin rejuvenation to date. In contrast, facial lipofilling to restore loss of volume seems to be promising.
Keywords: lipofiling; lipografting; fat grafting; facial-skin rejuvenation; mesenchymal stem cells; adipose-derived stromal cells; adipose tissue; skin quality; volume enhancing; stromal vascular fraction; cell-assisted lipotransfer